Doubt in the Insula: Risk Processing in Obsessive-Compulsive Disorder - Luigjes, Judy; Figee, Martijn; Tobler, Philippe N.; van den Brink, Wim; de Kwaasteniet, Bart; van Wingen, Guido; Denys, Damiaan (Frontiers in Human Neuroscience, 2016)
Extensive cleaning or checking of patients with obsessive-compulsive disorder (OCD) are often interpreted as strategies to avoid harm and as an expression of the widespread belief that OCD patients are more risk-averse. However, despite its clinical significance, the neural basis of risk attitude in OCD is unknown. Here, we investigated neural activity during risk processing using functional magnetic resonance imaging and simultaneously assessed risk attitude using a separate behavioural paradigm in OCD patients with different symptoms versus healthy controls. We found opposite insula responses to high versus low risk in OCD patients compared to healthy controls: a positive correlation between insula activity and risk-aversion in patients versus a negative correlation in controls. Although OCD patients overall were not more risk-averse than controls, there were differences between subgroups of OCD patients: patients with doubt/checking symptoms were more risk-averse than other patients. Taken together, OCD patients show a reversed pattern of risk processing by the insula compared to healthy controls. Moreover, the data suggest that increased activation of the insula signals an abnormal urge to avoid risks in the subpopulation of OCD patients with doubt and checking symptoms. These results indicate a role for the insula in excessive risk-avoidance relevant to OCD.